Improving Citrus Nitrogen Uptake Efficiency: Linking Citrus Irrigation Management To Citrus Fertilizer Practices - Kelly T. Morgan; Edward A. Hanlon (EDIS)
SL-246, a 6-page fact sheet by K. T. Morgan and E. A. Hanlon, matches irrigation management with nitrogen fertilization practices, explains the components of an effective irrigation system for citrus, and describes nutrient management planning and the possible roles for precision agricultural techniques. Published by the UF Department of Soil and Water Sciences, February 2007.